The Role of Patient and Parent Education in Pediatric Cast Complications. (September 2022) - Kearney, Lauren; Thompson, Julie; Zychowicz, Michael; Shaw, Ryan; Keyes, Sean
Abstract : Cast immobilization remains the standard of care in managing pediatric fractures. Cast complications often result in emergency department visits, office calls and visits, or lasting patient morbidities that burden the healthcare institution from a time and economic standpoint. The purpose of this quality improvement project was to create a multimodal cast care education protocol with an aim of decreasing cast complications over a 6-week period. Qualified patients (0–18) placed in cast immobilization received a quick response (QR) code sticker on their casts linked to a custom cast care website with text, pictures, and video instructions. Incidence of cast complications, complication type, effect(s) on workflow, and patient demographics were recorded. The complication rate declined 7.6%, but it was not statistically significant. Continuous access to clinic-specific cast instructions demonstrates decreased cast complications in pediatric populations, and this approach to patient education can be easily utilized across all medical specialties.